(untitled) (Journal of Philosophy Culture and Political Science, 2019)
Abstrast. The Basic Law of the Republic of Kazakhstan declared a secular state in which the highest values are recognized a person’s life, rights and freedoms, including freedom of conscience, which can only be limited when their exercise violates the rights and freedoms of other persons, infringe on the constitutional order and public morality. The country is fl ooded with various kinds of missions, previously unknown in Kazakhstan. An increase in inter-religious tensions caused by the struggle for inclusion in the numbers of new supporters. Contributes to the exacerbation of active work in the country of foreign agents, which, with its considerable fi nancial resources and extensive experience in missionary work, often pushing aside the traditional religions in Kazakhstan in the struggle for infl uence over the faithful. Although sectarian confl ict so far, as a rule, do not lead to any anti-social acts, appearing mainly in the criticism of his rivals as «false prophets» in the prayer meetings, in public utterances of the clergy, the very intensity of it is quite alarming symptom. By itself, nonideological religion does not pose a security risk. As the former chairman of the KNB Nurtai Abykayev in the Republic, the number of foreign religious missions, visiting the Republic in order to spread the religious and mystical teachings and create conditions for confl ict on religious and ethnic basis.